Effect of nanoparticulate copper, zirconia and graphite: contribution to the friction coefficient and transfer layer formation in dry sliding tests with interfacial media addition. - Rodrigues, Ana Cecilia Pontes (2019)
Copper is present in brake pads in the form of fibres, tough its suppression from pads\' formulations is already a trend compared to the suppression of asbestos in the 1980\'s. As a contribution to this challenging scenario, this work investigated the behaviour of mixture additions containing copper, zirconia, graphite and magnetite in dry sliding tribotests. Pin-on-disc tribotests with interfacial media addition were performed in order to contribute on the mission of understanding how Cu, graphite and ZrO2 particles act on the oxide transfer layer formation on dry sliding conditions. Thus describing some of the tribological properties that a possible replacement for copper in brake pads should mimic. Tests were performed at 23°C in air, 400°C in air and 400°C in N2. Nanoparticulate Cu, ZrO2 and micron-sized graphite were mixed in a Fe3O4 basedmatrix. The ZrO2 particles were incorporated to the mixtures by two mixing methods: manual mixing and high-energy ball milling. This study sought to explain the coefficient of friction (CoF) behaviour of these additions individually, as well as together, by correlating the CoF with comprehensive characterization of the oxide transfer layer. The transfer layer was characterized by means of scanning electron microscopy (SEM), Focused Ion Beam (FIB) and Transmission electron microscopy. Graphite containing mixtures displayed low average CoF values (0.23 to 0.31) due to selective transfer of graphite films to the first bodies\' tribosurfaces. Copper formed agglomerates and patches within the oxide transfer layer that were responsible for raising the CoF values at 23°C and acted as soft copper films at 400°C. The nanoparticulate addition of ZrO2 in the manual mixtures prevented the formation of Cu patches and larger agglomerates, promoting the formation of a smooth and compact oxide tribolayer, though graphite\'s selective transfer was still observed.